Exploration of the food environment in different socioeconomic areas in Hong Kong and Singapore: a cross-sectional case study - Ivan Ho; Tricia Chng; Sue Kleve; Tammie Choi; Julie Brimblecombe (BMC, 2023)
Abstract This study explored the local food environment of Hong Kong and Singapore using a qualitative case study approach to inform future upstream public health nutrition policies. Food outlets that provide food to be eaten in the home were mapped in selected areas of high and low socioeconomic status (SES) of Hong Kong and Singapore. Food outlet density relative to land area was determined. In both countries, lower SES areas surveyed were shown to have higher food outlet density while higher SES areas had fewer but larger food outlets. In Hong Kong, both SES areas reported similar proportions of healthy and unhealthy food outlets. This study highlights the accessibility of food outlet types through their geographical location and density. Future research assessing the differences in eating culture between these two countries should be considered alongside this study's findings, to investigate strategies influencing the food environment in order to promote healthier eating habits.